Peningkatan Kinerja pada Departemen Mold and Tooling Preparation di PT. X - Deny Pradwita Kristanto; Felecia Felecia (Jurnal Titra, 2022)
PT. X is a company engaged in the production of packaging such as compacts, bottles, tubes, and jars. The packaging produced will be used for packaging various kinds of cosmetics. During the production process this company experienced problems with high item rejects and downtime rates caused by workers doing many activities that did not provide added value (NVA), therefore the company wanted to improve the performance of workers. The purpose of this study is to provide an effort to improve the performance of the MTP Department using the Daily In The Life Of (DILO) method. The DILO method is used to analyze all the activities of a worker during his working hours. The DILO method is carried out in several stages including analysis of time composition, workload, and actual job description. The results obtained through the analysis where MTP workers have an average NVA activity value of 44.37% and the value of other items of 38.77%. From the results of the analysis, suggestions for improvement will be given by providing solutions to improve the performance of the MTP Department workers at IMM EBM